2005
DOI: 10.1523/jneurosci.2093-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Identification of Concurrent Sounds in the Owl's Auditory Space Map

Abstract: In nature, sounds from multiple sources sum at the eardrums, generating complex cues for sound localization and identification. In this clutter, the auditory system must determine "what is where." We examined this process in the auditory space map of the barn owl's (Tyto alba) inferior colliculus using two spatially separated sources simultaneously emitting uncorrelated noise bursts, which were uniquely identified by different frequencies of sinusoidal amplitude modulation. Spatial response profiles of isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…Effects of this kind have been observed in single neurons of regions as diverse as cortical area MT (Britten and Heuer, 1999; Heuer and Britten, 2002) and inferior colliculus (Keller and Takahashi, 2005). They may be due to normalization operating in the population responses in those regions or in earlier stages.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of this kind have been observed in single neurons of regions as diverse as cortical area MT (Britten and Heuer, 1999; Heuer and Britten, 2002) and inferior colliculus (Keller and Takahashi, 2005). They may be due to normalization operating in the population responses in those regions or in earlier stages.…”
Section: Discussionmentioning
confidence: 99%
“…When two sources concurrently emit sounds with overlapping amplitude spectra, the frequency-specific binaural cues assume values that are the average of each individual source’s cues weighted by their amplitudes. Thus, if one of the two sources momentarily achieves a higher amplitude than the other, the binaural cues approximate the values of the higher-amplitude source for that moment (Blauert, 1997; Keller and Takahashi, 2005; Snow, 1954; Takahashi and Keller, 1994). A space map neuron is therefore likely to fire when the amplitude modulation at a given instant favors the target, which is in its SRF, over the masker.…”
Section: Resultsmentioning
confidence: 98%
“…Although the two sounds’ carriers were identical, the 3-ms delay causes segments of the waveform in the leading source to align with segments in the lagging source that were 3 ms earlier and were therefore statistically uncorrelated in their fine-structure. Earlier studies have shown that the owl’s auditory system represents two, concomitant, uncorrelated noises as separate foci of activity on its auditory space map and that a delay of about 0.1 ms (100 μs) is sufficient to cause such decorrelation (Keller and Takahashi, 1996a, 2005). Thus, the decorrelated fine-structure allows two separate foci to form, while the envelope determines their relative strengths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ITD and ILD alone are sufficient to drive orienting behavior [8,21], owls as well as mammals can also rely on spectral cues for locating and identifying sound sources in space [22,23]. It has been shown that midbrain space-specific neurons display frequency dependent tuning to ITD and ILD [24,25].…”
Section: Emergence Of a Map Of Auditory Spacementioning
confidence: 99%